2018
DOI: 10.1002/zamm.201800091
|View full text |Cite
|
Sign up to set email alerts
|

A refined two‐dimensional theory for thermal bending of functionally graded plates with thickness normal strains

Abstract: A refined theory is presented for the thermal response of composite functionally graded plates under thermo‐mechanical loads. The theory includes shear deformation and normal strain effects by assuming through‐the‐thickness linear in‐plane displacements and parabolic transverse displacement. A mixed variational approach is used to introduce stresses satisfying the loading conditions on the plate surfaces without employing any shear correction factor used in other theories of the same order. A thermal bending p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They found that the GPLs distribution pattern affect significantly the buckling mode. Fares et al [10] proposed a refined two-dimensional theory to analyze thermal bending of FG plates with thickness normal strains. Song et al [11] examined the bending and the buckling of GPL reinforced composite plates.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the GPLs distribution pattern affect significantly the buckling mode. Fares et al [10] proposed a refined two-dimensional theory to analyze thermal bending of FG plates with thickness normal strains. Song et al [11] examined the bending and the buckling of GPL reinforced composite plates.…”
Section: Introductionmentioning
confidence: 99%